Will the landscape composition and socio-economic development of coastal cities have an impact on the marine cooling effect?. (February 2023) - Chen, Lisu; Qi, Qiuyu; Wu, Huafeng; Feng, Daolun; Zhu, Enyan
Highlights: An estimate of the marine cooling effect (MCE) in coastal cities was conducted. The sea cools urban with the greatest intensity in spring, followed by summer. Coastal cities have the best cooling intensity near the coastline for 5 km. Heterogeneous effects of natural and socio-economic factors on MCE were studied. High vegetation helps to abnormal temperature, as opposed to impervious surfaces. Abstract: The marine plays an important role in mitigating air and land surface temperatures (LST) in coastal cities, but its influences and main contributions remain unknown. This study assessed the marine cooling effect (MCE) on coastal cities in the Yangtze River Delta (YRD) region during spring, summer, and autumn. Then, the heterogeneous effect of landscape composition, socio-economic development, and meteorological conditions on the MCE was investigated by using geographically weighted regression (GWR) models. The results show that the MCE has significant spatial and temporal heterogeneity, with the strongest marine cooling intensity (MCI) in spring (8.95–22.92 °C), followed by summer (0.48–15.88 °C) and autumn (-1.43–9.98 °C). The marine influence is greatest in the 5 km area near the coastline, and the cooling range is shorter in summer. Furthermore, high vegetation cover, diversity of land types, and complexity of the landscape shape contribute to the increased cooling range (MCD) and mitigation LST. Although areas with intensive and connected impervious surfaces increase the LST and obtain higher MCI, they prevent cold air from penetrating deeper inland. To be noticed, MCE is better in areas with better economic development and higher population density. These findings provide new perspectives for climate adaptation planning and design practices in urban coastal areas.